We Only Accept Online Applications: The Effect of HRIS E-Recruitment Technology on Job-Seeker Fairness Perceptions in the Canadian Federal Public Sector - Wesolowski, Peter (Université d'Ottawa / University of Ottawa, 2016)
Industrial-organizational psychologist Stephen S.W. Gilliland developed a model for studying job-seeker fairness perceptions in 1993 based on existing research in organizational justice. The model includes several rules which will result in job-seeker perceptions of fairness if satisfied and job-seeker perceptions of unfairness if violated. Given the prominence of this model in the literature as well as changes which have occurred in personnel selection (such as human resource information systems, or HRIS, and e-recruitment), scholars have called for a technological re-envisioning of the original model, especially the explanations/descriptions ascribed to each rule. The present study seeks to understand how HRIS e-recruitment technology impacts job-seeker fairness perceptions and in so doing update the Gilliland (1993) model using a qualitative methodology and website success measures from information systems success theory. It contributes to the literature on applicant fairness perceptions by accounting for technological change, and contributes to the field of Public Administration by studying a governmental e-recruitment portal thereby accounting for the particularities of public-sector HRM which is underrepresented in the organizational justice literature. Over the course of one (1) year, twelve (12) job-seekers participated in a series of focus group interviews where they reflected on their experiences applying for jobs in the Canadian federal civil service using the government’s e-recruitment portal. Participants completed profiles, sent applications, communicated with government personnel, and wrote internet tests, among other job-search activities, and reported on their experiences from the perspective of fairness. Results confirm the validity of all original procedural justice rules and offer insight into their application in a recruitment environment where applicants invest considerable time interacting with computerized systems. Two additional rules are also put forth including the ease with which candidates can deceive tests and privacy/trustworthiness using technology. The findings are limited insofar as data gathering took place during a time of reduced hiring activity by the employer and because participation was limited to one (1) specific geographic location.
Keywords: Fairness perceptions; Job-search; Applicant reactions; Organizational Justice; Industrial-Organizational Psychology; Employment Search; E-Recruitment; Human Resources Information Systems; Public Service Commission; Public Administration; Information Systems Success Theory; Procedural Justice; Personnel Selection; Staffing; Government of Canada; Unsupervised Internet Testing; Focus Group